Geometrical characteristics and kinetic mechanism of the fault system in the centre of Hanoi trough and their role in the formation and destruction of Cenozoic structural traps - Hoang Huu Hiep; Nguyen Huu Nam (Petrovietnam Journal, 2014)
The fault system in the centre of Hanoi trough includes Vinh Ninh fault, Thai Binh fault and the high order faults between them. These faults belong to Song Hong fault system - a well-known deformation zone in South Asia consisting of ductile and brittle deformations with very diff erent kinetic mechanisms. In this paper, the authors analysed the geometrical characteristics and the kinetic mechanisms of the fault system of the centre of Hanoi Trough and pointed out their role and infl uences on the formation and destruction of structurally reversed hydrocarbon traps.